GIVING SUPPLEMENTS THROUGH DRINKING WATER WITH DIFFERENT DOSAGE AGAINST PRODUCTIVITY OF CHICKEN LOHMAN BROWN - I K. A., Arsana; Astawa, I P. A.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika, 2020)
The study aims to determine the effect of supplementation through drinking water at different doses on the productivity of lohman brown chicken. The study was conducted in Candikusuma Village, Melaya District, Jembrana, Bali, for 3 months, from data collection to thesis data analysis. The design used in the study was a Completely Randomized Design (CRD) with three treatments and five replications. The treatments given are: chickens that get drinking water without supplementation as a control (P0), chickens that get drinking water with the addition of 0.05% supplement (P1), and chickens who get drinking water with the addition of 0.1% supplement (P2 ). The variables observed in the study were ration consumption, drinking water consumption, hen day production (HDP), total egg weight, average egg weight and ration conversion. The results showed that drinking water consumption, hen day production (HDP), total egg weight and average egg weight in P1 and P2 treatments were significantly higher (P <0.05) compared to chickens that received control treatment (P0) while consumption ration and ration conversion decrease. Based on the results of the study it can be concluded that supplementation through drinking water with different doses of 0.05% and 0.1% significantly increases drinking water consumption, hen day production (HDP), total egg weight and average egg weight and significantly decreases ration consumption and conversion ration.   Keywords: Lohman brown hen, productivity, supplements.